The Challenges of Substance Use Disorders in Neurology - Kiteva Trenchevska, Gordana; Ignjatova, Liljana (World Association on Dual Disorder, 2023)
Introduction. Despite addiction and substance use disorders (SUD) being brain disorders, neurologists lack the knowledge to recognise the risks for developing SUD and addiction from certain prescribed drugs among persons with different neurological disorders, especially those who suffer from neuropathic pain, fibromyalgia, and headaches. These conditions may be associated with anxiety, depression, behaviour dis- orders, somatic, psychological and cognitive disability, social misfunction, dual disorders and impaired life quality. The aim is to address the challenges of SUD in neurology. Neurological manifestations in SUD are due to either chronic substance use, intoxication, or withdrawal. The dopaminergic, cholinergic, endoge- nous cannabinoid and opiate neurotransmitter pathways participate in SUD in neurology and psychiatry/ psychology. Methods. 15 patients, with a mean age of 41 years SD 4.7, with SUD- opiate users, were referred to neurology, and ten others without a known diagnosis of SUD, for clinical, neurophysiological, and imaging evaluation. Results. The complaints of most of them were muscle pain, neck pain, gait impair- ment, peripheral sensory nerve deficits in the legs, low back pain, and lumbar radiculopathy. Four patients from the group with SUD manifested seizures, and despite seizures should be recognised as provoked SUD- seizures, antiseizure medicament (ASM) was prescribed in one case. Eight patients had seizures from the group with an unknown diagnosis of substance use. Still, when the diagnosis of provoked seizures was established from anabolic steroids, opiate analgesics, benzodiazepines, and illegal drugs, it resulted in a referral to an addictologist without ASM prescription or ASM withdrawal to prevent unnecessary drug load and drug interaction. Two patients with SUD had a loss of consciousness due to a drug overdose. Although people who use alcohol, excluded in this analysis, are easily recognised by neurologists when in a coma or impaired consciousness, it is not the case in other SUD. Addiction and SUD may mimic different neurological disorders. It was when opiate overdose was wrongly assumed to be a myasthenic respiratory crisis with consequent intubation and artificial respiration. Conclusions. Neurological mimics and neurological and neuropsychological comorbidities are frequent conditions in SUD besides psychiatric. A holistic approach from a knowledgeable team of a neurologist, psychiatrists, psychologists, social workers, geneticists, and special services is a need for appropriate diagnosis, treatment, and prevention to decrease the quality of morbidity and mortality in SUD and improve life quality.
Keywords: substance use; pain; provoked seizures; impaired consciousness